Satisfaction levels in patients attending an ophthalmology service in a level II hospital between 2014 and 2018, and their relationship with overall quality - Mendoza, Nora B. (2020)
Objective: to compare satisfaction levels of patients regarding quality of care in the ophthalmology service in a level II hospital between 2014 and 2018, and also, to determine overall quality in 2018. Materials and methods: this is an observational, cross section and analytical study. The sample comprised 678 patients, and two instruments were used: SERVQUAL, which measures satisfaction levels in five quality dimensions, and SERVQHOS, which measures the overall quality of services used. Results: in 2014, subjects (n= 346) interviewed with the SERVQUAL instrument declared being “satisfied” with the quality of care they received, particularly with respect to safety; but, in 2018, subjects (n= 332) declared their satisfaction levels were reduced in all scenarios. With respect to SERVQHOS, most subjects declared being satisfied with the overall quality of services and said they would recommend this hospital to other persons. Their encounters had enough time, healthcare personnel performed tests after asking for permission, subjects knew the names of physicians taking care of them, and they also said they received adequate information about their health condition. A weak association between SERVQUAL and SERVQHOS was found, which was directly proportional between patient satisfaction levels and overall quality. Conclusion: during 2014, patients declared “being satisfied” with the quality of care they received compared to 2018, when they declared being “mildly unsatisfied”. When overall quality was measured, patients declared being satisfied, emphasizing medical care and respect towards them.